"Good" Grief: Subversion, Praxis, and the Unmasked Ethics of Griefing Guides. Issue 3 (2nd July 2016) - Beale, Matthew; McKittrick, Megan; Richards, Daniel
ABSTRACT: This article uses genre-field analysis (GFA) to examine Minecraft griefing guides: user-generated documentation that operationalizes destructive approaches to gameplay. Griefing guides promote subversive praxis while forwarding a utilitarian ethical system that alues hedonistic schadenfreude, running counter to morals of cooperation championed by most Minecraft players. Published in online forums where debates over conflicting praxis continue, these guides explicitly address, rather than mask, the negotiation of ideological values and ethical systems within a community.